Ethiopian Women, the Law of Safuu, and Ecofeminist Climate Justice in Genesis 2 - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
Mainstream eco-theological readings of Genesis 2:4–17 have emphasized “stewardship” or “dominion” without engaging African Indigenous legal systems or the concrete climate knowledge of Ethiopian women. The Oromo moral-ecological law of Safuu, a system of prohibitions against pollution, deforestation, and over-extraction remains largely absent from biblical interpretation and climate justice discourse. This article advances an Ethio-ecofeminist reading of Genesis 2:4–17, arguing that the creation narrative, interpreted through Safuu and the lived agency of Ethiopian women as seed-keepers, water fetchers, and sacred-grove guardians, yields a juridical-ecological mandate for climate justice. The study employs decolonial feminist biblical criticism and Oromo epistemology, conducting a verse-by-verse exegesis of Genesis 2:4–17 alongside ethnographic and policy analysis of Ethiopian women’s climate burdens, the Gadaa governance system, and forest carbon offset schemes. Findings: The Hebrew adam-adamah kinship resonates with Oromo Uumaa (creation as family); the prohibition of the tree of knowledge functions as a Safuu boundary protecting interdependence; and the mandate to avad and samar (to till and to keep) charges humans with sacred service and protective guardianship. Ethiopian women’s watershed councils, seed cooperatives, and liturgical forest rituals enact this mandate against extractive agriculture and carbon offset projects that displace them. Conclusion: Genesis 2, read through Safuu and Ethiopian women, replaces the “dominion” model with an indigenous, gendered framework for climate justice grounded in communal land trusts, water commons, and restorative enforcement. Policy makers should recognise women’s Idir assemblies as official water governance bodies, mandate free prior informed consent for forest carbon projects, and integrate Safuu-based dispute resolution into land administration.